THE VALIDITY OF MARRIAGE THROUGH “ITSBAT NIKAH” ACCORDING TO THE PERSPECTIVE OF THE PEOPLE OF KUTOREJO VILLAGE, KEPAHIANG, BENGKULU REGENCY - Ainalmardhiaturrahman Ainalmardhiaturrahman (Jurnal Al-Dustur, 2022)
The Research is motivated by the phenomenon of massive sirri marriage in the village of Kutorejo Kepahiang, yet the legalization rate is still few. This is contrary to the Law. This research aims to contribute to the community to understand that marriage has been regulated in the Law so that the number of marriages can be suppressed and immediately strive for legalization. This thesis is a type of field research with descriptive qualitative writing methods and a normative sociological approach with legal theory. In collecting data, the author makes observations and interviews and then describes the data further analyzed according to the Law. The research concluded that the number of Itsbat Nikah  is inversely proportional to the number of sirri marriages in Kutorejo village due to the public’s lack understanding of government laws and programs. There is no absolute socialization of the village in bridging the recording of sirri marriages. The motives of the community in applying for marriage licenses vary, including ease of access to public services, legal status rights of marriage, property rights to inheritance rights so that people's views on the legalization of marriage are pursued.